2021
DOI: 10.3389/fonc.2021.585006
|View full text |Cite
|
Sign up to set email alerts
|

Application of Gross Tissue Response System in Gastric Cancer After Neoadjuvant Chemotherapy: A Primary Report of a Prospective Cohort Study

Abstract: ObjectiveWe previously established a gross tissue response (GTR) system to evaluate the intraoperative response of perigastric tissue in patients with gastric cancers to neoadjuvant chemotherapy. This prospective cohort study aims to confirm the relationship between gross tissue response and clinicopathological characteristics and explore the possibility of using the GTR system to predict the difficulty of surgery and the occurrence of postoperative complications within 30 days.MethodsA total of 102 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…We found that patients after NACT were more prone to suffer from concomitant tissue severe edema, fibrosis, and effusion, and the normal and customary anatomical layer was also defunct, especially for the suprapancreatic area. We also established a gross tissue response (GTR) system to predict the risk of a difficult operation after NACT and postoperative complications [ 31 ]. Higher GTR sore was associated with surgical trauma and postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…We found that patients after NACT were more prone to suffer from concomitant tissue severe edema, fibrosis, and effusion, and the normal and customary anatomical layer was also defunct, especially for the suprapancreatic area. We also established a gross tissue response (GTR) system to predict the risk of a difficult operation after NACT and postoperative complications [ 31 ]. Higher GTR sore was associated with surgical trauma and postoperative complications.…”
Section: Discussionmentioning
confidence: 99%